2017
DOI: 10.1088/2053-1583/aa8442
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable photoconductivity and mobility enhancement in printed MoS 2 /graphene composites

Abstract: Aiming to increase carrier mobility in nanosheet-network devices, we have investigated MoS2-graphene composites as active regions in printed photodetectors.Combining liquid-exfoliation and inkjet-printing, we fabricated all-printed photodetectors with graphene electrodes and MoS2-graphene composite channels with various graphene mass fractions (0≤Mf≤16wt%). The increase in channel dark conductivity with Mf was consistent with percolation theory for composites below the percolation threshold. While the photocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
(105 reference statements)
3
13
1
Order By: Relevance
“…composites. 21 Here we found the carrier density data above the percolation threshold to be consistent with percolation-scaling:…”
Section: Electrical Properties Of 2d;2d Compositessupporting
confidence: 70%
See 1 more Smart Citation
“…composites. 21 Here we found the carrier density data above the percolation threshold to be consistent with percolation-scaling:…”
Section: Electrical Properties Of 2d;2d Compositessupporting
confidence: 70%
“…21 This would be an important development which would be of use in the area of printed electronics using 2D materials. [22][23][24][25][26] A number of papers have described printed electronic devices such as photodetectors, 21 switches, 23 memory elements 25 and transistors 22,27 which are predominately based on networks of 2D nanosheets. However, nearly all such devices are limited by relatively low mobilities which tend to be ~0.1 cm 2 /Vs for printed networks of transition metal dichalcogenide nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…22 The conductivity is also 20 times higher than that found for MoS 2 on paper 20 and 100 times larger than the higher conductivity values reported for conductive networks of liquid phase exfoliated MoS 2 . [23][24][25] Nonetheless the conductivity of the WS 2 -on-paper films is still lower than the in-plane conductivity of bulk (∼10 2 S m −1 ) 26 and mechanically exfoliated single-layer WS 2 (∼10 3 S m −1 ), 27 indicating a large contribution of the out-of-plane transport as well as the flake-to-flake hopping in the total conductivity of the WS 2 films on paper. In the ESI † a transfer length measurement on a WS 2 film on paper is described to extract the contact resistance and the conductivity.…”
Section: Thermoresistive Characteristics Of the Ws 2 -On-paper Devicesmentioning
confidence: 89%
“…For these reasons, standard device fabrication approaches, developed and optimized for the fabrication of devices on silicon substrates, cannot be directly used on paper substrates. New fabrication techniques have been developed in the last years to overcome that issue, and now vdW materials can be deposited onto paper substrates using inkjet printing of inks prepared by liquid-phase exfoliation 7,[11][12][13][14][15][16][17][18][19] or by a recently reported all-dry abrasion-induced deposition method. 20,21 Up to now these methods already demonstrated that one can fabricate heterostructures and pattern complex devices, with high spatial resolution, with conducting, semiconducting and insulating vdW materials on paper.…”
Section: Introductionmentioning
confidence: 99%